Early Bronchoalveolar Lavage among Patients with Severe Traumatic Brain Injury and Predicted Macro-Aspiration - Chaudhuri, Pratyush Nirmal Kusum (Indian Journal of Neurotrauma, 2015)
Problems Considered The severity of brain injury and the outcome of therapy have a direct correlation to the presence of aspiration pneumonitis and aspiration pneumonia. Patients often develop macro-aspiration immediately following trauma. This study proposes to evaluate the outcome of check bronchoscopy after severe head injury and develop a scoring system to determine the most likely candidate who would benefit from the procedure.Method Total 30 patients were prospectively observed after check bronchoscopy for outcome with regard to pneumonia and survival.Results The procedure could be safely performed in all the 30 patients and the findings were suggestive of significant particulate aspirate. The Predictor of Macro-Aspiration at Trauma site [PMAT] was an effective tool to identify the potential candidates.Conclusion Check bronchoscopy and lavage may be helpful in decreasing the burden of infection and thereby improve outcome. The PMAT score may be an effective tool to triage the patients who need bronchoscopy.
Keywords: macro-aspiration; aspiration pneumonia; bronchoscopy in neurotrauma